Comparison Between Different Diameter and Length of Pile Foundation on Its Bearing Capacity in Soft Soils Using Plaxis 2D Software Modeling - Tiyo, Yien; Lim, Alvin John (Recent Trends in Civil Engineering and Built Environment, 2023)
The pile designs with different diameter and length affect its ultimate bearing capacity in marine clay. The marine clay which often found in Malaysia especially at the coastal area are considered as problematic soil type due to its low strength and high compressibility’s properties. Many development projects on the marine clay area requires suitable pile foundation design to ensure a strong support to the superstructure. This study will help to determine the best pile design with greatest ultimate bearing capacity by analysing, predicting and comparing the bearing capacity of different pile designs. The Finite Element Analysis (FEA) of Plaxis 2D software was used in this study to help simulate the models of pile and marine clay under load application. Soft Soil Model and Linear Elastic Model were adopted for the simulation of 15 pile models of different length and diameter ranging from 6m to 46m (in length) and 0.3m to 1.0m (in diameter). Chin’s method was used to predict the ultimate bearing capacity based on the load-settlement curve. The results show that the bigger the pile diameter, the greater its ultimate bearing capacity. Also, the longer the pile length, the greater its ultimate bearing capacity. As a result, the pile model P (1.0m, D and 46m, L) with ultimate bearing capacity of 2000kN was the best pile design in marine clay.